Neutralization of endogenous IL-1 receptor antagonist exacerbates and prolongs inflammation in rabbit immune colitis. - Ferretti, M (1994)
Administration of exogenous interleukin-1 receptor antagonist (IL-1ra) is effective in reducing the severity of disease in animal models of acute inflammation. However, the function of endogenous IL-1ra in this process, is not yet known. We investigated the pathophysiological role of IL-1ra in a rabbit model of formalin-immune complex colitis. This model has previously been shown to be IL-1 mediated and a reduction in disease severity is observed with exogenous IL-1ra treatment. Colonic IL-1ra was found to be elevated subsequent to IL-1, and exceeded IL-1 levels 10-fold. Peak levels of IL-1ra preceded both the resolution of colitis and a significant decrease in IL-1 production. Administration of specific neutralizing antibodies against rabbit IL-1ra increased mortality and prolonged intestinal inflammatory responses. A significant increase in IL-1 alpha colonic tissue levels was also measured as a result of exogenous anti-IL-1ra treatment. These studies are the first demonstration that endogenous IL-1ra may play an important role in regulating the host's inflammatory response by counteracting the deleterious and possibly lethal effects of IL-1 produced during acute inflammation.